Linking proactive personality and entrepreneurial intentions: A serial mediation model involving broader and specific self-efficacy - Shumaila Naz; Cai Li; Umer Zaman; Muhammad Rafiq (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Entrepreneurial intention (EI) has been widely cited as one of the foremost predecessors of entrepreneurship which fosters business opportunities to minimize the dependence on employment. Since it is worth noticing how one's EI is formed; therefore, the prime purpose of this paper is to estimate the underlying concepts of proactive personality (PP) in establishing potential entrepreneurs' EI through the mediating role of both specific self-efficacy and broader self-efficacy. This research investigates the parallel mediation and the role of mediators in the form of a series between PP and EI via broader self-efficacy and specific self-efficacy. The extant research employed a quantitative methodology by using a self-administered questionnaire technique. Data were collected using the cluster sampling technique from a sample size of 700 respondents in the higher education sector. To test the measurement and structural modeling, the PLS-SEM technique was deployed using Smart PLS 2.0 M3 software. Regarding the direct relationships, findings infer that PP is positively associated with three broader forms of self-efficacy, which determine specific self-efficacy. Findings indicated that broader forms of self-efficacy and specific self-efficacy play the role of the serial mediators in the relationship between proactive personality and entrepreneurial intentions. The research carries important implications for the university policymakers in Pakistan to develop their self-reliant "business incubation centers", initiate experiential learning-based projects, improvise competency-based curriculum, design innovative projection techniques, and follow open innovation dynamics to establish an entrepreneurial culture.
Keywords: 650; creative self-efficacy; entrepreneurial intentions; entrepreneurial self-efficacy; leadership self-efficacy; learning self-efficacy; proactive personality